Sociodemographic and Reproductive Factors Associated with Breast Cancer: A Case-Control Study in a Cancer Specialized Hospital of Dhaka City, Bangladesh (Delta Medical College Journal, 2022)
Background: Breast cancer is the most common cancer in women in the world. In Bangladesh, the breast cancer is estimated to have the age-standardized incidence rate of 25.2 per 100,000 females of all ages.Objective: The objective of this study was to identify the sociodemographic and reproductive factors associated with the development of breast cancer in Bangladesh.Materials and method: A case control study was conducted on 136 female subjects, in a cancer specialized hospital of Dhaka city (68 subjects for case group with breast cancer and 68 subjects for control group without any known cancer) aged ≥20 years. Data was collected by face to face interview with structured questionnaire. The results were reported by adjusted odd ratios (ORs) and corresponded 95% confidence intervals (CIs). A p-value less than 0.05 were considered statistically significant. Independent factors associated with breast cancer were established using multivariate logistic regression analysis.Result: Among the reproductive factors, women with the history of hysterectomy are 84% less likely and post-menopausal women are 27.83% more likely to get breast cancer. On sociodemographic background women who received 12+ years of schooling and 6 to 10 years of education are 14.91% and 4.91% more likely to get breast cancer. Women with the monthly family income of 5000 Tk to 25000 Tk are 76% less likely to get breast cancer than women with more monthly family income. Women married for more than 20 years are 7.27% more likely to get cancer. Women with 3 or more children are 81% less likely to get breast cancer than women with fewer children.Conclusion: Our study suggests that, age, level of education, monthly family income, history of hysterectomy of the patient may play an important role in risk of breast cancer in Bangladeshi women. Further research is needed to better understand the complex interactions between environmental, reproductive and genetic factors.Delta Med Col J. Jul 2020 8(1): 4-8